Transcriptomic Profiling of Misgurnus anguillicaudatus Reveals the Anti-Inflammatory Action of Lonicera japonica Extract in Response to Lipopolysaccharide Challenge - Yue Zhao; Chen Wang; Qiuning Liu (Fishes, 2025)
Honeysuckle, derived from the dried flower buds or blossoms of Lonicera japonica Thunb, is a traditional Chinese medicine known for its properties in eliminating heat and toxins, reducing inflammation, and alleviating swelling. In this study, we investigated the potential therapeutic and preventive benefits of L. japonica extract on inflammatory diseases induced by lipopolysaccharide (LPS) using Misgurnus anguillicaudatus as a model organism. The fish were fed a diet supplemented with L. japonica extract, followed by LPS injection to induce inflammation. We then analyzed the transcriptional profile to identify differentially expressed genes (DEGs). A total of 6611 DEGs were identified through comprehensive analysis, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. Our results revealed significant enrichment of DEGs in pathways associated with proteasome function, immune system regulation, and infectious disease response. These findings suggest a strong correlation between L. japonica and immune defense mechanisms, providing valuable insights into the potential anti-inflammatory effects of this plant, particularly in the context of LPS-induced inflammation. This study highlights the potential use of L. japonica in treating inflammatory diseases and underscores its role in immune regulation.